KAJIAN ON JOB TRAINING PT. ANGKASA PURA I BANDAR UDARA JENDERAL AHMAD YANI SEMARANG - Puput Ayu Ningrum (Jurnal Pengabdian Masyarakat Waradin, 2021)
This activity has the intention that students gain experience before entering the real world of work, so that students will get provisions and lessons from the On The Job Training that has been carried out. With On The Job Training, students will know the skills and knowledge that need to be developed. One of the efforts to improve human resources, especially in higher education is through internships which are an important means for self-development in the real world of work. General Ahmad Yani International Airport is one of the airports air which is managed by PT. Angkasa Pura I (Persero) as the gateway and spearhead of air traffic located in the western part of the city of Semarang